Infectious Pustular Vulvovaginitis in a Buffalo: A Case Report - Narang , Asmita; Sharma , A. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present communication reports a case of infectious pustular vulvo-vaginitis in a 5 year-old Murrah buffalo. The animal had a history of abortion, retention of foetal membranes and dark, raised nodular lesions on the surface of udder with mastitis. Physical examination revealed a rectal temperature of 104 ℃ and slightly congested mucous membranes. On examination of the vaginal mucous membranes, several white, round lesions were observed. Dark circular, raised lesions were observed on the surface of the udder as well. On haematological examination it was found that there was presence of absolute neutrophilia with a mild left shift. The impression smear from vaginal mucous membrane revealed hyperplastic changes with presence of few neutrophils. The CMT score of all quarters were 2+, with pustular discharge observed from the right hindquarter. The animal was treated with Ceftiofur (1.1 mg/kg BW), gentamicin (4.4 mg/kg BW) and metronidazole (10mg/kg BW) along with b-complex vitamins and supplements containing biotin and vitamin A. The animal recovered uneventfully.